Vibrational analysis of the low-temperature modification of the chloride spinels : Li2MCl4 (M = Fe, Co and Cr) - Heyns, A.M. (University of Pretoria, 2024)
Dissertation (MSc (Chemistry))--University of Pretoria, 1992.